A NEBA- AHP Decision Framework for Sustainable Remediation of Petroleum-Contaminated Soils: A Case Study from Tropical Oil Palm Plantations in Indonesia - Nur Septiani; Herto Dwi Ariesyady; Qomarudin Helmy (Jurnal Serambi Engineering, 2026)
This study developed and demonstrated an integrated NEBA–AHP framework for selecting remediation technologies at four petroleum-contaminated sites in active palm oil plantations at four sub-areas in Bengkalis Regency, Riau Province. This study integrates Net Environmental Benefit Analysis (NEBA) and Analytic Hierarchy Process (AHP), as the quantitative component, and guided interviews with 20 respondents across four sub-areas as the qualitative component. Four remediation alternatives were evaluated. The proposed framework consistently discriminated between remediation alternatives across all sub-areas: bioremediation received the highest NEBA-AHP score, while ISCO and excavation with backfilling (Dig & Fill), despite the highest technical effectiveness, were consistently penalized for physical disturbance and socioeconomic disruption. Stakeholders showed strong agreement across sub-areas in ranking preferences and rated bioremediation significantly more acceptable than enhanced natural attenuation. These results illustrate how the framework balances technical, environmental, and social criteria to identify context-appropriate remediation strategies, here favoring bioremediation under the evaluated conditions. The NEBA-AHP framework is transferable to other contaminated sites, provided that criterion weights are re-elicited through local expert panels reflecting site-specific regulatory, ecological, and socioeconomic conditions.